Interventions to support the mental health and well-being of front-line healthcare workers in hospitals during pandemics: an evidence review and synthesis. Issue 11 (7th November 2022) - Robins-Browne, Kate; Lewis, Matthew; Burchill, Luke James; Gilbert, Cecily; Johnson, Caroline; O'Donnell, Meaghan; Kotevski, Aneta; Poonian, Jasmine; Palmer, Victoria J
Abstract : Objective: Pandemics negatively impact healthcare workers' (HCW's) mental health and well-being causing additional feelings of anxiety, depression, moral distress and post-traumatic stress. A comprehensive review and evidence synthesis of HCW's mental health and well-being interventions through pandemics reporting mental health outcomes was conducted addressing two questions: (1) What mental health support interventions have been reported in recent pandemics, and have they been effective in improving the mental health and well-being of HCWs? (2) Have any mobile apps been designed and implemented to support HCWs' mental health and well-being during pandemics? Design: A narrative evidence synthesis was conducted using Cochrane criteria for synthesising and presenting findings when systematic review and pooling data for statistical analysis are not suitable due to the heterogeneity of the studies. Data sources: Evidence summary resources, bibliographic databases, grey literature sources, clinical trial registries and protocol registries were searched. Eligibility criteria: Subject heading terms and keywords covering three key concepts were searched: SARS-CoV-2 coronavirus (or similar infectious diseases) epidemics, health workforce and mental health support interventions. Searches were limited to English-language items published from 1 January 2000 to 14 June 2022. No publication-type limit was used. Data extraction and synthesis: Two authors determined eligibility and extracted data from identified manuscripts. Data was synthesised into tables and refined by coauthors. Results: 2694 studies were identified and 27 papers were included. Interventions were directed at individuals and/or organisations and most were COVID-19 focused. Interventions had some positive impacts on HCW's mental health and well-being, but variable study quality, low sample sizes and lack of control conditions were limitations. Two mobile apps were identified with mixed outcomes. Conclusion: HCW interventions were rapidly designed and implemented with few comprehensively described or evaluated. Tailored interventions that respond to HCWs' needs using experience co-design for mental health and well-being are required with process and outcome evaluation.